Confucianism and sacred space: the Confucius temple from imperial China to today - Huang, Jinxing (Columbia University Press, 2021)
"Confucianism and Sacred Space uses the site of the Confucius temple to explore Confucianism both as one of China's "three religions" (with Buddhism and Daoism) and as a cultural phenomenon, from the imperial era and to its secular garb under the Communists. This translation draws on Chin-shing Huang's two monographs and numerous published articles to provide a holistic picture of his decades-long research into Confucius temples. An introduction gives a historical overview and pulls the pieces together"--